Tree composition of cocoa associated species: Lacandon jungle and agroforestry systems, Chiapas, Mexico - Avendaño Arrazate, Carlos Hugo (2021)
Introduction. The tree composition associated with creole cocoa and that developed in cocoa production systems is different. This information is important to adopt future strategies in conservation and improvement programs. Objective. Contribute to the knowledge about the tree composition of species associated with creole cacao in Mexico. Materials and methods. The data analyzed in this study included variables of the horizontal and vertical structure, in addition to the diversity of tree species associated with cocoa under different conditions. This study was carried out during May to September 2018, in plots where creole cacao trees were found in their natural habitat in the Lacandona jungle and in cacao plantations in three locations in Soconusco, in Chiapas, Mexico. In them, the tree species were counted and taxonomically classified. Results. Associated with the creole cacao in the Lacandon jungle, twenty-one species were registered, which were grouped into nineteen genera and thirteen families, whose abundance, richness and density was greater than that registered in cocoa production systems in the Soconusco region, which contributed to a difference between both ecosystems with only two shared species. Conclusion. The abundance, richness, and density of tree species associated with creole cocoa was higher than that registered in the production systems, with dissimilarity in their conditions. Differences were recorded in the location of the cocoa crop within the vertical structure of both scenarios studied.